Effects of atorvastatin on some inflammatory markers in patients with multiple sclerosis treated by interferon beta-1b - Farah Waleed Mahmood; Shamil Hashim Othman (المجلة العراقية للصيدلة, 2019)
Objective: To investigate the effect of Atorvastatin vs. placebo on some inflammatory markers in patients with multiple sclerosis treated by interferone beta-1b.To achieve the aim of this study, a randomized control comparative trial was adopted. Patients and Methods: A total of 100 patients with multiple sclerosis were recruited and investigated for some inflammatory markers which included, interleukin-2, tumor necrosis factor-α, C-reactive protein, and erythrocyte sedimentation rate. The patients were divided into 2 groups, namely the atorvastatin group which consisted of 50 patients and the placebo group which consisted of 50 patients. The patient groups were followed- up for 12 weeks during which the above parameters were measured before starting therapies and at the end of the follow-up period using commercially available kits. The patient groups were compared with the control group consisted of 50 apparently healthy subjects. Results: The IL-2,TNF-α,CRP and ESR at baseline in both patient groups were found significantly elevated as compared with the control group ( p< 0.001) . The use of atorvastatinhas resulted in significant decrease on the above parameters with non-significant effects in the placebogroup. Atorvastatinappeared to be superior in compared with the placebo group. Conclusion: The use of atorvastatinfor 12 weeks in patients withmultiple sclerosis treated by interferone-beta has beneficial effect on some inflammatory markers studied in this research( IL-2,TNF-α,CRP and ESR).